2012
DOI: 10.22146/ajche.50060
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Physical Properties And Mathematical Modeling Of Thin-Layer Drying Kinetics Of Medium And Long Grain Parboiled Rice

Abstract: This research was to investigate some thermo-physical properties and to determine a mathematical model for describing drying kinetics for medium and long grain parboiled rice varieties. The thermo-physical properties in terms of equilibrium moisture content (EMC), apparent density, void fraction, specific heat capacity at moisture content ranging from 30 to 58% dry-basis (d.b.) for both Leb Nok Pattani (LNP) and Suphanburi 1 (SP 1) rice varieties were determined by conventional standard techniques.The evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…1). Previous work explained that the increase in apparent density with increasing moisture content was mainly due to an increase in volume that is less than the corresponding increase in mass of the material [5].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…1). Previous work explained that the increase in apparent density with increasing moisture content was mainly due to an increase in volume that is less than the corresponding increase in mass of the material [5].…”
Section: Resultsmentioning
confidence: 91%
“…The measurements were repeated five times for each moisture content level. Void fraction of the corn seed was then calculated by following previous work [5].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…However, Byler et al (1987) reported that this commonly used drying model for thin-layer was inadequate for modeling parboiled rice. Bualuang et al (2011) developed a mathematical model to describe the drying kinetics of medium and long-grain parboiled rice. They found that the Guggenheim-Anderson-de Boer (GAB) model best fit the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The best-fitted model would show the highest R 2 and the lowest χ2 according to CIE L*, a*, and b* parameters.The baked samples were spread thinly in a petri dish, and the color sensor (Precision colour meter, China) was pointed at the samples, and care was taken to make sure it was covered fully.Bulk density was determined by putting the baked worm samples in a 250 ml measuring cylinder. The bulk density was calculated by dividing the mass (M) with the volume (V) using equation 12. measured based on the length of the baked worm using a vernier calliper.…”
mentioning
confidence: 99%